Adapting selection strategies of executors of business processes based on profit and social qualities. (October 2017) - Hacid, Hakim; Ugljanin, Emir; Sellami, Mohamed; Maamar, Zakaria
Abstract: This paper discusses an approach for selecting executors of business processes based on profit and social-quality criteria. The approach relies on a trusted authority to ensure the transparency and fairness of the selection. Executors are known as slaves and exhibit certain social qualities (e.g., selfishness and goodwill) in response to the requests of owners of business processes known as masters. A set of simulation tests are carried out to demonstrate the feasibility of the approach in term of what selection strategy is best, i.e., profit-based, social quality-based, or both.